FEATURES OF ARCHITECTURAL FORMS OF BUDDHIST TEMPLE COMPLEXES IN THE TERRITORY OF THE CHANG'AN-TIEN SHAN CORRIDOR OF THE GREAT SILK ROAD - Hailong Cao (Архитектон, 2022)
Analysis of the monastic complexes of the Tang Dynasty located in the territory of the Chang'an-Tien-Shan corridor of the Great Silk Road allows us to see how the existing planning and artistic solutions of Chinese architecture are combined with the traditions of Buddhist architectural thought, and how architectural forms are transformed under the influence of natural, socio-cultural and political conditions. Monastic complexes in China and modern Kazakhstan were chosen as objects of study, which enabled the main features of the cult architecture of the Tang period to be identified.